Correlation of transcutaneous bilirubin with total serum bilirubin in neonates with hyperbilirubinemia - Venkatesan, Mohanram; Russelian, Arulraj; Velimuthu, Palpandi (International Journal of Contemporary Pediatrics, 2021)
Background: For determining hyperbilirubinemia in a neonate, clinical evaluation, serum bilirubin estimation and trans cutaneous bilirubin estimation are the modalities available. Transcutaneous bilirubinometry (TcB) is routinely used to monitor jaundice in term and near-term infants. Literature shows a positive correlation observed between TcB and total serum bilirubin (TSB). The present study was conducted determine the correlation of TcB with TSB in neonates with hyperbilirubinemia admitted at a tertiary care hospital, Chennai Methods: A cross sectional study was conducted at a tertiary care hospital, Chennai where 350 neonates who have clinical jaundice and require estimation of serum bilirubin who are admitted to the tertiary care centre, Chennai during December 2020-March 2021 were included in the study. The ROCHE INTEGRA-e 411+ autoanalyzer was used to estimate TSB (mg/dl) using a modified diazo method. The Jaundice Meter JM-103 to measure TcB, (Manufactured by Draeger medical systems, Germany). Pearson corelation coefficient was used to find the correlation between the two variables. P<0.05 was considered to be statistically significant. Results: Out of 350 neonates admitted to the tertiary care centre, term deliveries were 57.1% and pre term were 42.9%. 83.1% were in the age group of 3-7 days. The mean weight of the study population was 2.16±0.60 kg. In term babies, Pearson corelation between TSB and TcB shows a statistically significant positive correlation, r=0.90 with p≤0.0001. Among pre term babies, Pearson corelation between TSB and TcB shows a statistically significant positive correlation, r=0.96 with p≤0.0001. Conclusions: This study’s findings support the use of a TcB metre as a screening tool for clinically significant hyperbilirubinemia.